India and ADB three decades of enduring partnership. (Development Effectiveness Brief., 2018)
This publication examines how ADB operations have improved people lives in India and looks at the challenges that ADB and India face in pursuing agreed development goals.The ADB Results Framework indicators are used to report the bank country level performance in this Development Effectiveness Brief, which complements the annual Development Effectiveness Review.